Nitric oxide and anglotensin II receptors mediate the pressor effect of angiotensin II: A study in conscious and zoletil-anesthetized rats - Guarda, Ismael F. M. S.; Saad, Wilson A.; de Arruda, Luiz Antonio (Lippincott Williams & Wilkins, 2007)
The circumventricular structures of the central nervous system and nitric oxide are involved in arterial blood pressure control, and general anesthesia may stimulate the central renin-angiotensin system. We therefore investigated the central role of angiotensin 11 and nitric oxide on the regulation of systemic arterial blood pressure in conscious and anesthetized rats. METHODS: Rats with stainless steel cannulae implanted into their lateral ventricle were studied. We injected the AT(1) and AT(2) angiotensin 11 receptor antagonists, losartan and PD123319, L-NAME, 7-nitroindazole (nitric oxide synthetase inhibitors), and FK409 (nitric oxide donor agent) into the lateral ventricles. Mean arterial blood pressure (MAP) was recorded in conscious and zoletil-anesthetized rats. RESULTS: Mean +/- (SEM) baseline MAP was 117.5 +/- 2 mm Hg. Angiotensin II injected into the brain lateral ventricle increased MAP from 136.5 +/- 2 min Hg to 138.5 +/- 4 mm Hg (Delta 16 +/- 3 mm Hg to Delta 21 +/- 3 mm Hg) for all experimental groups versus control from 116 +/- 2 mm Hg to 120 +/- 3 mm Hg (Delta 3 +/- 1 mm Hg to A5 +/- 2 mm Hg) (P < 0.05). L-NAME or 7-nitroindazole enhanced the angiotensin II pressor effect (P < 0.05). Prior injection of losartan and PD123319 decreased the angiotensin 11 pressor effect and the enhancement effect of L-NAME and 7-nitroindazole (P < 0.05). Zoletil anesthesia did not interfere with the effects of angiotensin 11, AT,, AT2 antagonists, or nitric oxide synthetase inhibitors. CONCLUSIONS: Endogenous nitric oxide functions tonically as a central inhibitory modulator of the angiotensinergic system. AT, and AT2 receptors influence the angiotensin 11 central control of arterial blood pressure. Zoletil anesthesia did not interfere with these effects. (Anesth Analg 2007;105:1293-7)